MULTIPLIER EFFECTS OF PESANTREN WALINDO - Ismanto, Kuat; Nasrullah, M. (IAIN Surakarta, 2019)
This study aims to investigate the multiplier effects of business run by pesantren in economic, education, and social fields. It is a field research conducted in Pesantren Walindo, Siwalan district, Pekalongan. By using qualitative approach, the data were collected through observation, interview, and documentation. The presence of the researcher was the key point in obtaining the data. The deep interview was conducted to some related parties, such as kyai, managers, and santri (students). This study reveals several findings. First, there is significant effect of developing business in Pesantren Walindo on its development and independence because it can cover 60% of operational funding without drawing fee from the santri. Second, related to the business units development, this pesantren is able to strengthen the sense of entrepreneurship in santri?s spirit. The business unit management run by the santri along with kyai and nyai build their business awareness which can be their foundation after they graduate from this pesantren. Third, regarding the social filed, the relationship between the pesantren and the society are conducted both in the form of partnership and other kinds of relationship which bears the sense of belonging of the society toward the pesantren and their trustworthy to register their children there. Keywords: pesantren, multiplier effects, pesantren business units